Les institutions dans la théorie de la régulation : une actualisation - Bernard Billaudot (Revue de la Régulation)
The research programme on regulation has progressed through two stages. The first stage is devoted to an “institutionalist” mark of the programme, by placing the emphasis on analysis of institutional forms conceived as codification of one or of several social relations which constitute capitalism. The second stage is more specific about this definition. The institutions are analysed as a mediation between the structure and the individual behaviour i.e. articulation between instituting collective action and individual action. This paper sums up the situation of this second stage about the characteristic of the socio-economic structure in question and about the accurate content to give to the term of mediation. This updating makes the common base of the two areas of research stand out and determines an institutionalism with its own identity in regard to other institutionalisms which have appeared in economics during the last thirty years.